Royal Concubinage in Ngaoundere, Northern Cameroon, ca. 1900–1960 - Sinderud, Marte Bogen (The International journal of African historical studies, 2013)
"13 I will nevertheless use it as an analytical concept, given that the female section of the Ngaoundere palace shared similar features with royal harems in other parts of the Sokoto Caliphate and beyond. [...]in this article, the word harem refers to the secluded palace interior, that is the part of the palace containing the family quarters of the laamiido (pi. laamiibe), reserved for himself, his legally wedded wife or wives, concubines, his daughters and prepubescent sons.14 The palace harem also included concubines of former laamiibe, who were allowed to live there in their old age, as well as female menial slaves.15 Occasionally, other female relatives of the laamiido resided in the palace harem too. First of all, the possibility of royal concubines to exercise influence largely hinged on their personal relationship with the ruler.